2021
DOI: 10.1108/srj-06-2021-0220
|View full text |Cite
|
Sign up to set email alerts
|

Environmental corporate social responsibility initiatives and green purchase intention: an application of the extended theory of planned behavior

Abstract: Purpose This study aims to integrate the perspective of consumer social responsibility with the theory of planned behavior to explore the impact of environmental corporate social responsibility (ECSR) initiatives on intention to buy environmentally friendly products among Vietnamese consumers. Also, the moderating role of gender on the associations of antecedents and green purchase intention is tested in this study. Design/methodology/approach The data of 823 consumers using the tool of the mall-intercept su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 87 publications
5
61
0
2
Order By: Relevance
“…Finally, as a vindication of prior research findings in workplace environmental citizenship behavior and consumer green purchase intentions [ 24 , 66 ], results of this research demonstrated that perceived ECSR significantly enhances residents’ private and public environmental citizenship behavior (H8, H9). This means that when residents receive environmental stimuli from the destination (e.g., perceived ECSR), they respond to this stimulus in a positive manner, i.e., performing environmental citizenship behavior.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Finally, as a vindication of prior research findings in workplace environmental citizenship behavior and consumer green purchase intentions [ 24 , 66 ], results of this research demonstrated that perceived ECSR significantly enhances residents’ private and public environmental citizenship behavior (H8, H9). This means that when residents receive environmental stimuli from the destination (e.g., perceived ECSR), they respond to this stimulus in a positive manner, i.e., performing environmental citizenship behavior.…”
Section: Discussionsupporting
confidence: 64%
“…In an attempt to reveal why Pakistan manufacturing sector employees behave sustainably, researchers obtained similar findings [ 24 ]. Moreover, in the green consumption context, Vu et al (2021) discovered that there is a significant and positive relationship between ECSR initiatives and green purchase intentions among Vietnamese consumers [ 66 ]. However, to the best knowledge of this research team, this study is one of the first empirical efforts to explain how perceived ECSR affect environmental citizenship behavior among residents in rural destinations.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In this regard, evidence in the literature shows that individuals with a positive attitude toward the environment are more willing to perform pro-environmental activities and behaviors [ 55 , 56 , 57 ]. Furthermore, a positive relationship between becoming aware of the environment’s protection and manifesting an attitude toward its care has been reported [ 23 , 58 , 59 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous research commenced by Choo et al, (2004), Aksoy and Abdulfatai (2019), , Jain (2020), , Vu et al, (2021), and Chen and Wang (2021) had underlined the positive and significant impact given by subjective norm on consumers' purchase intention, in which, consumers' intention to purchase certain products were strongly and significantly determined or influenced by how consumers perceive the others' judgements or comments toward the buying behavior which was going to be conducted by consumers themselves. In this case, the chance that consumers will have a strong intention to buy the product or service will be higher if consumers felt that such buying behavior will be viewed positively or favorable by the others.…”
Section: H2: Perceived Price Had a Significant Effect Toward Consumer...mentioning
confidence: 99%